An extensive investigation on gamma shielding properties of PLA/Gd2O3 nanocomposites - Niksarlioglu, Secil; Akman, Ferdi; Pekdemir, Mustafa Ersin; Kuzu, Serpil Yalcin; Kacal, Mustafa Recep; Yilmaz, Mucahit (Pergamon-Elsevier Science Ltd, 2023)
This paper presents the gamma shielding performance of Poly lactic acid (PLA) composites doped with 4%, 8%, 12%, and 16% Gd2O3 to investigate the impact of dopant amount on gamma shielding with an energy of 241Am (59.5 keV), 133Ba (81.0, 276.4, 302.9, 356.0, 383.9 keV), 22Na (511.0,1274.5 keV), 137Cs (661.7 keV), and 60Co (1173.2, 1332.5 keV) sources. To characterize the radiation shielding properties of the samples, mass attenuation coefficient (mu/rho), linear attenuation coefficient (mu), half-value layer (HVL), tenth-value layer (TVL), and effective atomic number (Zeff) parameters were calculated and compared with the values computed by WinXCOM soft-ware. It is revealed that theoretical and experimental results are in agreement and the radiation protection ef-ficiency was enhanced with the increase of the dopant amount. Radiation effects on the structure and thermal stability of the samples were also studied by Attenuated total Reflectance-Fourier transform infrared spectros-copy (ATR-FTIR) measurements and thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The spectroscopy results showed a remarkable decrease in the absorbance value of the composites after gamma irradiation.
Keywords: Gamma ray shielding; Poly lactic acid (PLA); Nanocomposites; Thermal stability; Shape memory